SUNFLOWER CULTIVATION USING MICRO-FERTILIZERS AND BACTERIAL PREPARATIONS - Kovalenko, O. A.; Fedorchuk, M. I.; Neroda, R. S.; Donets, J. L. (Scientific Progress & Innovations, 2020)
The article presents the results of research as to the influence of different fertilization backgrounds on productivity and phenological parameters of Limagrain Tunka sunflower hybrid under the conditions of natural moisturizing of the Southern Steppe of Ukraine. In the research conducted on the fields of the educational-scientific-practical center of Mykolaiiv National Agrarian University, the issues of affecting and combining the complex of highly concentrated chelate fertilizer, mono-element micro-fertilizer and functional micro-fertilizer with directed specific action of Quantum trademark produced by the scientific-production complex “Kvadrat” and Bio-complex-BTU-r nutrition and disease prevention bio-preparation produced at the enterprise of “BTU-Center” company were studied. The scientific work was carried out using pre-sowing treatment of sunflower hybrid seed material, foliar fertilization of plants with different rates of mixed bio-preparation with a complex of micro-fertilizers in the phase of 5-6 leaves, in the phase of 9-10 leaves and double spraying of crops in the phases of 5-6 and 9-10 leaves. The duration of the period from sowing to harvesting of the studied sunflower hybrid depending on influencing factors varied from 2 to 13 days as compared with the control area, and plant height during flowering period increased under the influence of the applied experimental factors from 4.37 % to 13.1 %. There was a clear tendency to increasing the diameter of the of hybrid plants’ heads depending on the experimental factors, with the maximum combination of pre-sowing seed treatment and foliar fertilization in two phases of development. The maximum increase in size was 28.7 %. In accordance with changing the conditions of foliar fertilization, yield indicators of the hybrid seeds also changed, so crops with a combination of seed treatment and double fertilization formed the highest yield. These figures ranged from 1.81 to 2.54 t/ha. The change in the quantitative and qualitative composition of the used forms of preparations led to changing oil content in sunflower seeds. Conditional yield of crude sunflower oil, at the maximum rate of applying the complex of Quantum micro-fertilizers and Bio-complex-BTU-r bio-preparation in the combination with pre-sowing treatment of hybrid seeds, with double foliar fertilization of plants in phases of 5-6 and 9-10 leaves, was maximum, and had an increase of 0.424 t/ha as compared with the control.